Upstream Stimulatory Factor Regulates Major Histocompatibility Complex Class I Gene Expression: the U2ΔE4 Splice Variant Abrogates E-Box Activity - Howcroft, T. Kevin (American Society for Microbiology, 1999)
The tissue-specific expression of major histocompatibility complex class I genes is determined by a series of upstream regulatory elements, many of which remain ill defined. We now report that a distal E-box element, located between bp −309 and −314 upstream of transcription initiation, acts as a cell type-specific enhancer of class I promoter activity. The class I E box is very active in a neuroblastoma cell line, CHP-126, but is relatively inactive in the HeLa epithelial cell line. The basic helix-loop-helix leucine zipper proteins upstream stimulatory factor 1 (USF1) and USF2 were shown to specifically recognize the class I E box, resulting in the activation of the downstream promoter. Fine mapping of USF1 and USF2 amino-terminal functional domains revealed differences in their abilities to activate the class I E box. Whereas USF1 contained only an extended activation domain, USF2 contained both an activation domain and a negative regulatory region. Surprisingly, the naturally occurring splice variant of USF2 lacking the exon 4 domain, U2ΔE4, acted as a dominant-negative regulator of USF-mediated activation of the class I promoter. This latter activity is in sharp contrast to the known ability of U2ΔE4 to activate the adenovirus major late promoter. Class I E-box function is correlated with the relative amount of U2ΔE4 in a cell, leading to the proposal that U2ΔE4 modulates class I E-box activity and may represent one mechanism to fine-tune class I expression in various tissues.